MTOR activation in CD8+ cells contributes to disease activity of rheumatoid arthritis and increases therapeutic response to TNF inhibitors. (13th November 2021) - Zhang, Mingzeng; Iwata, Shigeru; Sonomoto, Koshiro; Ueno, Masanobu; Fujita, Yuya; Anan, Junpei; Miyazaki, Yusuke; Ohkubo, Naoaki; Sumikawa, Maiko Hajime; Todoroki, Yasuyuki; Miyata, Hiroko; Nagayasu, Atsushi; et al.
Abstract: Objective: This study aimed to understand the role of mammalian target of rapamycin (mTOR) in CD8 + cells in the pathogenicity of RA and the changes after treatment with biologic drugs. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from 17 healthy controls and 86 patients with RA. Phosphorylation of mTOR (p-mTOR) and its clinical relevance were evaluated. The role of mTOR in CD8 + cells was also examined in vitro . Results: Patients with RA who had a moderate or high disease activity, were biologic-naïve, and were refractory to MTX were enrolled in this study. The p-mTOR levels in CD8 + cells were higher in patients with RA than in healthy controls, and they positively correlated with the disease activity in such patients. However, after one year of treatment with TNF inhibitors, the p-mTOR levels in CD8 + cells were suppressed and showed a positive correlation with the treatment response, which was not observed in the abatacept-treatment group. In vitro stimulation of CD8 + cells with anti-CD3 and anti-CD28 antibodies induced mTOR phosphorylation and increased the production of granzyme B, granulysin, TNF-α and IFN-γ but decreased the production of granzyme K. However, on treatment with TNF inhibitors, p-mTOR levels in CD8 + cells and granzyme B production decreased, while granzyme K production increased. The production of granulysin and IFN-γ was not affected by the TNF inhibitors. Conclusion: These results suggested that mTOR activation in CD8 + cells may be a novel evaluation marker for RA disease activity and a predictive marker of therapeutic response to TNF inhibitors.